Determinants of attitude and intention of bank employees towards conversion to full-fledged Islamic banking in Libya - Mohamed A. M. Abdelrahim, El-Brassi; Syed Jaafar Alhabshi, Syed Musa; Othman, Anwar Hasan Abdullah (2019)
This study seeks to identify the factors influencing bank employees’ attitude and intention towards converting to full-fledged Islamic banking (IB) in Libya. It adopts a model based on the Theory of Planned Behaviour (TPB) to identify the predictors of attitude and intention towards conversion to the IB system. The data consist of 323 self-administered questionnaires collected from bank employees of conventional banks (CBs) in Libya. The data were then subjected to analysis employing structural equation modelling (SEM). We found that knowledge of Islamic banking products and religiosity were strong determinants of bank employees’ attitude towards conversion. Attitude and subjective norms also significantly affect bank employees’ intention. The outcomes offer Libyan policymakers, regulators and bank managers better understanding of the roles played by the religious factor, knowledge of IB products and social values in influencing the attitude and intentions of Libyan bank employees concerning the conversion The findings should be considered to design and develop policy regulations and strategies to enhance the IB industry in Libya.